CONSCIÊNCIA HISTÓRICA E NARRATIVA: UM ESTUDO SOBRE ORIENTAÇÃO TEMPORAL DE ESTUDANTES DA EDUCAÇÃO BÁSICA - Hass, Gláucia Marília (2011)
This investigation had as object the orientation way of historical sense from students in their relation with the language. The research has as theoretical fundament the studies of narrative and of historical consciousness by Paul Ricoeur and Jörn Rüsen. The study tried to answer the following questions: what are the representations of future revelead through the time articulations made by the historical consciousness manifested in the narratives of young students of fundamental and middle learning levels? In what degree can we identify in the narratives the attribution of historical sense to the experience as a way of practical life orientation of the students? The objective of this study is to identify the attribution of historical sense to the experience as a mean of practical life orientation of the students through the analysis of their visions of future described by them in written productions. For this purpose, a data search was made in two state schools in the city of Ponta Grossa, with primary and secondary level students that gave those informations through the construction of written and oral narratives. In all, five groups of informants were formed: three with written narratives and two with oral narratives, obtained through the technique of focal group. The research has qualitative nature and for the data treatment was followed the methodology of content analysis, as proposed by Laurence Bardin. As conclusions we presented the students difficulty in project themselves in time as caused above all by a grammatical difficulty in the application of the verbal times into action, lack of empathy capacity and, identity crisis and of the public power action related to consumerism conditions.